PROFIL KONDILOMA AKUMINATA DI POLIKLINIK KULIT DAN KELAMIN RSUP PROF.DR. R.D. KANDOU MANADO PERIODE JANUARI 2012 - DESEMBER 2012 - Nelwan, Stella R.; Niode, Nurdjannah J.; Kapantow, Marlyn G. (e-CliniC, 2014)
Abstract: Condyloma acuminata, also known as genital warts, is a vegetation of certain types of Human Papilloma Virus(HPV), stalky with bumpy surface. This disease is a sexually transmitted disease, most HPV infections in anogenital area are acquired during sex. This was a descriptive retrospective study, where the data were collected from medical records and registers book of sexually transmitted disease (STD) in Dermatovenereology clinic of Prof. Dr. R. D. Kandou Hospital Manado. The result showed that in 2012, there were 27 new cases of condyloma acuminata, 2.46% of all new patients Most age group found was 25-44 years which was 13 patients (48.15%), with sex distribution mostly found in female patients which was 14 patients (51.85%). Most occupation found was private employees by 10 patients (37.04%). Most affected locations in female patients was vulva and vulva with vagina by 5 patients each of them (35.71%), where as in male patients was penis which was found in 4 patients. The result also showed that HIV was the most comorbid disease found in 3 patients (11.11%). Conclusion: In this study, most condyloma acuminata patients is in 25-44 age group, mostly found in female, most occupation was private employee, most location affected in female were vulva and vulva with vagina, while in male patients was penis, most therapy used was podophyllin. Most comorbid disease was HIV. Keywords: Condyloma acuminata, Human papilloma virus, female Â Â Abstrak: Kondiloma akuminata (KA) adalah vegetasi oleh Human Papilloma Virus (HPV) tipe tertentu, bertangkai dengan permukaannya berjonjot. Penyakit ini tergolong infeksi menular seksual, kebanyakan infeksi HPV di daerah anogenital didapatkan melalui hubungan seksual. Penelitian ini bersifat deskriptif retrospektif; data diambil dari rekam medik dan buku register infeksi menular seksual bagian ilmu penyakit kulit dan kelamin RSU Prof. Dr. R. D. Kandou Manado. Hasil penelitian memperlihatkan pada tahun 2012 dari total kunjungan baru terdapat 27 kasus baru KA (2,46%). Kelompok umur terbanyak didapatkan adalah 25-44 tahun sebanyak 13 orang (48,15%) dengan jenis kelamin terbanyak perempuan sebanyak 14 orang (51,85%) Pada pekerjaan terbanyak pada pekerja swasta sebanyak 10 orang (37,04%) Lokasi lesi pada perempuan tersering di vulva dan vulva ditambah vagina masing-masing sebanyak 5 orang (35,71%), sedangkan pada laki-laki tersering di penis yaitu sebanyak 4 orang. Hasil penelitian juga didapatkan penyakit penyerta terbanyak adalah HIV sebanyak 3 orang (11,11%) . Simpulan: Dalam Penelitian ini, pasien KA terbanyak pada kelompok umur 25-44 tahun paling banyak pada perempuan, jenis pekerjaan pegawai, lokasi lesi pada perempuan tersering pada vulva dan vulva ditambah vagina sedangkan pada laki-laki tersering di penis, pengobatan tersering podofilin. Penyakit penyerta ada lah HIV. Kata kunci: Kondiloma Akuminta, Human papilloma virus, Perempuan.